2018
DOI: 10.1186/s12955-018-1042-4
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life when a partner has substance use problems: a scoping review

Abstract: ObjectiveTo examine the existing body of knowledge on quality of life (QoL) in partners of people with substance use problems (PP-SUPs) to provide a synthesized summary of the evidence and identify gaps in our knowledge on the QoL of PP-SUPs.MethodsA systematic scoping review was performed. Publications indexed in EMBASE, Medline, PsycINFO, CINAHL, SocINDEX, and CENTRAL were searched for original, empirical, peer-reviewed, full-length research papers that examined QoL in PP-SUPs. Research papers identified thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 41 publications
1
34
1
Order By: Relevance
“…In light of Birkeland and colleagues' () finding of an association between problem severity of the person using substances and the CO's poorer quality of life, it was perhaps surprising that we did not find support for this association. Similar to our study, however, spouses’ alcohol consumption was unrelated to the other spouse's subsequent depression symptoms (Homish et al., ).…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…In light of Birkeland and colleagues' () finding of an association between problem severity of the person using substances and the CO's poorer quality of life, it was perhaps surprising that we did not find support for this association. Similar to our study, however, spouses’ alcohol consumption was unrelated to the other spouse's subsequent depression symptoms (Homish et al., ).…”
Section: Discussioncontrasting
confidence: 73%
“…Quality of life is now one of the most common indicators of functioning, as it utilizes respondents’ perceptions and expectations to capture the lived experiences of addiction, treatment, relapse, and recovery (Laudet et al., ; Muller et al., ). A review reported that most of 9 studies of partners of people with substance use problems found that partners have a lower quality of life than the general population (Birkeland et al., ).…”
Section: Cos’ Functioningmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was part of an exploratory, cross-sectional, multi-centre study, the Children of Ill Parents (CHIP)-study [45], with data collected from patients that were parents, the other parent/adult [66–69], children and adolescents (8-18 years) [69–72], children’s teachers, health professionals treating the ill parents, health professionals in the role of CRP, managers/ leaders, and hospital coordinators (H-CRP) [11, 46].…”
Section: Methodsmentioning
confidence: 99%